A Quest For Islamic Paradigm:Towards The Production Of Islamic Knowledge - Khairulyadi, Khairulyadi (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2016)
This paper examines the deficiency of western paradigm in potraying human nature and thus proposes that there is a need for paradigmatic shifting if islamic methodology and knowledge is desired. While western based paradigm is helpful in underlining socially tangible context of human life, it fails to undestand human in its very nature. Those paradigms see human as, and confined to a mere bodily mundane creature but denying human intangible side, that human too is a spritual being. As a result, and due to differing principal and idiological standpoint, western paradigm is deemed inappropriate to grasp a full view of human nature as oppose to that of Islamic Tawhidic paradigm that sees human, by nature, as a material and non-material being. Hence, the Islamic paradigm is considered as an only paradigm applicable to, and suits the need of Islamic methodology in order to be able to produce Islamic knowledge. Key Words: Paradigm, Islamic Knowledge